Resource allocation theory applied to farm animal production [ - Rauw, Wendy Mercedes (CABI, 2008)
According to the Resource Allocation Theory, an individual's genetic potential can only be realized in an environment in which essential food resources are adequately supplied. This book describes resource allocation patterns in natural populations, th costs, preferences and trade-offs of maintenance, growth, reproduction and immune function.